2018
DOI: 10.1007/s00586-018-5717-7
|View full text |Cite
|
Sign up to set email alerts
|

Is vertebral body stenting in combination with CaP cement superior to kyphoplasty?

Abstract: Both techniques facilitated good clinical results in combination with absorbable cement augmentation. In particular, the VBS enabled us to benefit from the advantages of the resorbable isothermic CaP cement with an improved radiological outcome in the long term compared to BKP. However, there was a mentionable loss of reduction in the follow-up in both groups compared to previously published data with PMMA cement. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
3
18
1
Order By: Relevance
“…Schützenberger et al, in a retrospective study of 49 patients with osteoporotic compression fractures, compared the application of VBS® with kyphoplasty, both filled with calcium phosphate biological cement, and identified a significantly lower loss of vertebral height in the VBS® group throughout the mean follow-up period of 3.75 years (local kyphosis angle loss of 7.5⁰ ±4.8 in VBS® vs 10⁰ ±5.3 in kyphoplasty and Cobb angle loss of 6.5⁰ ±8 in VBS® vs 15.4⁰ ±11 in kyphoplasty) [ 53 ]. However, there were no differences in the capacity of initial vertebral reduction, in terms of clinical (VAS 2.0 ±2.3 vs 2.2 ±2.5) and functional (Oswestry 16.6 ±17.6 vs 16.7 ±19.7) parameters and in cement leakage rates (44% vs 23%) [ 53 ]. Garnon et al, in a retrospective case series of traumatic non-osteoporotic fractures treated with VBS®, found mean vertebral height gain, vertebral kyphosis angle correction, and Beck Index improvement of 3.8 mm, 4.3°, and 0.07, respectively [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…Schützenberger et al, in a retrospective study of 49 patients with osteoporotic compression fractures, compared the application of VBS® with kyphoplasty, both filled with calcium phosphate biological cement, and identified a significantly lower loss of vertebral height in the VBS® group throughout the mean follow-up period of 3.75 years (local kyphosis angle loss of 7.5⁰ ±4.8 in VBS® vs 10⁰ ±5.3 in kyphoplasty and Cobb angle loss of 6.5⁰ ±8 in VBS® vs 15.4⁰ ±11 in kyphoplasty) [ 53 ]. However, there were no differences in the capacity of initial vertebral reduction, in terms of clinical (VAS 2.0 ±2.3 vs 2.2 ±2.5) and functional (Oswestry 16.6 ±17.6 vs 16.7 ±19.7) parameters and in cement leakage rates (44% vs 23%) [ 53 ]. Garnon et al, in a retrospective case series of traumatic non-osteoporotic fractures treated with VBS®, found mean vertebral height gain, vertebral kyphosis angle correction, and Beck Index improvement of 3.8 mm, 4.3°, and 0.07, respectively [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…VBS can effectively restore and maintain the vertebral height, and has been widely used in the treatment of vertebral fractures. 22 , 27 Restoration of the vertebral body height can reduce the stresses on the adjacent endplates and decrease the risk of refracture. 28 In our study, postoperative vertebral height and Cobb angle were obviously improved.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Schutzenberger et al performed stentoplasty with CPCs to treat vertebral fracture which showed excellent clinical results, but height loss still existed. 22 The major disadvantage of CPCs is longer osteogenesis time and resulting weaker stiffness. In order to improve mechanical strength, two different methods are proposed: one is to improve primary stabilization through adding fiber reinforcements; and the other is to build secondary stabilization with callous tissue of new bone rapid formation.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo studies included 5 RCTs [ 14 , 20 , 23 , 25 , 26 ] and 6 retrospective cohort studies [ 18 , 19 , 24 , 32 – 34 ] involving 1035 patients with 1320 segments of diseased vertebral bodies. Among them, four trials [ 14 , 26 , 33 , 34 ] compared SpineJack with PVP or PKP, while four [ 18 20 , 32 ] compared VBS with PVP or PKP, and three [ 23 – 25 ] compared KIVA versus PKP.…”
Section: Methodsmentioning
confidence: 99%